Simulation of mechanisms for motion visualization - Gan, Ting Li (Nanyang Technological University, 2022)
3D printing is changing the way products are designed and manufactured. The quality and resolution of 3D printers have resulted in an increased interest in its use for the production of functional parts. However, there are many types of 3D printers with different specifications. In this project, the objective is to investigate the 3D printing of mechanisms and its associated parameters. In particular, the design of the revolute joints and the required tolerance or minimum clearance will be investigated first followed by the designing of complete linkages. The design of linkages as assembly by parts or as non-assembly form will also be analysed. The linkages will be 3D printed with different materials. Tests will be conducted for the linkages with different printing constraints in terms of motion of smoothness. From the test observations, it will be considered for the types of printing constraint to design and print a linear gripper mechanism. The outcome of the linear gripper is concluded to be versatile. However, there are still areas of improvement that can be made to the current design and should be undertaken in future works.